THE COUNTRY NAME AND POLITICAL RECONSTRUCTION OF AFGHANISTAN - Peitao, Huang (PEOPLE: International Journal of Social Sciences, 2024)
Looking back at the history of regime changes in Afghanistan, Afghanistan’s political reconstruction after political instability is often accompanied by renaming the country. This phenomenon reflects the close connection between political reconstruction and the name of the country. A hypothesis was proposed to explain this phenomenon: The renaming of the country is a microcosm of Afghanistan’s political reconstruction process. By analyzing the composition of the country’s name, we can generally understand the country’s political reconstruction process. The analysis of the country’s name helps to explain the results of the political reconstruction of Afghanistan in history and to make a reasonable prediction of the results of the ongoing political reconstruction. To test this hypothesis, this paper made a historical analysis of the period of the Afghan People’s Democratic Party in power and the US-backed bourgeois-democratic political period. It reviewed the composition of the country’s name and the goals and results of political reconstruction in these two historical periods. Finally, this paper, in light of the elements in the name of “The Islamic Emirate of Afghanistan”, envisioned the current Taliban-led political reconstruction in Afghanistan.